2007
DOI: 10.1152/jn.00394.2007
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Modulation Encoding in the Primary Auditory Cortex of the Awake Owl Monkey

Abstract: Many communication sounds, such as New World monkey twitter calls, contain frequency-modulated (FM) sweeps. To determine how this prominent vocalization element is represented in the auditory cortex we examined neural responses to logarithmic FM sweep stimuli in the primary auditory cortex (AI) of two awake owl monkeys. Using an implanted array of microelectrodes we quantitatively characterized neuronal responses to FM sweeps and to random tone-pip stimuli. Tone-pip responses were used to construct spectrotemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 80 publications
2
36
0
Order By: Relevance
“…Previous adaptation studies have demonstrated that prolonged exposure to auditory stimuli with changing frequency increases the threshold for frequency modulation (Gardner & Wilson, 1979;Green & Kay, 1973;Kay & Matthews, 1972;Kayahara, 2001;Masutomi & Kashino, 2013;Regan & Tansley, 1979;Shu, Swindale, & Cynader, 1993;Tansley & Suffield, 1983), supporting the existence of neural populations tuned to frequency modulation. Confirming this psychophysical inference, neurophysiological studies have found neuronal populations tuned to frequency-modulation in a direction-selective manner in cats (Mendelson & Cynader, 1985;Mendelson & Grasse, 1992;Mendelson, Schreiner, Sutter, & Grasse, 1993), monkeys (Atencio et al, 2007;L. Liang, Lu, & Wang, 2002;Tian & Rauschecker, 2004), guinea pigs (Zhao & Liang, 1996), and bats (Gordon & O'Neill, 1998), and in humans using neuroimaging techniques (Pardo & Sams, 1993;Sams et al, 1991).…”
Section: Introductionmentioning
confidence: 72%
“…Previous adaptation studies have demonstrated that prolonged exposure to auditory stimuli with changing frequency increases the threshold for frequency modulation (Gardner & Wilson, 1979;Green & Kay, 1973;Kay & Matthews, 1972;Kayahara, 2001;Masutomi & Kashino, 2013;Regan & Tansley, 1979;Shu, Swindale, & Cynader, 1993;Tansley & Suffield, 1983), supporting the existence of neural populations tuned to frequency modulation. Confirming this psychophysical inference, neurophysiological studies have found neuronal populations tuned to frequency-modulation in a direction-selective manner in cats (Mendelson & Cynader, 1985;Mendelson & Grasse, 1992;Mendelson, Schreiner, Sutter, & Grasse, 1993), monkeys (Atencio et al, 2007;L. Liang, Lu, & Wang, 2002;Tian & Rauschecker, 2004), guinea pigs (Zhao & Liang, 1996), and bats (Gordon & O'Neill, 1998), and in humans using neuroimaging techniques (Pardo & Sams, 1993;Sams et al, 1991).…”
Section: Introductionmentioning
confidence: 72%
“…New World monkey vocalizations (e.g., twitter calls), for example, have been shown to contain FM transitions with rates between 30 and 50 octaves per second (Atencio et al, 2007;Bieser, 1998;Cheung, Bedenbaugh, Nagarajan, & Schreiner, 2001;Nagarajan et al, 2002;Wang, Merzinich, Beitel, & Schreiner, 1995). The role of frequency sweeps in animal communication has also been studied to determine its effect on object identification and informational unmasking (e.g., in nonhuman primates; Egnor, Iguina, & Hauser, 2006;Egnor, Wickelgren, & Hauser, 2007;Petkov, O'Connor, & Sutter, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…About four decades ago, Whitfield and Evans (1965) reported the presence of multiple FM response types in cat primary auditory cortex (A1) and qualitatively categorized them into four classes: 1) the cells commenced firing as a FM tone crossed the boundary into its TRF and continued to fire until it left; 2) the cells started and ceased firing when FM tones were wholly within TRF; 3) the cells fired when the FM tone was outside TRF; 4) the cells responded to FM tones, but not to steady tones. The recent study on the A1 of awake monkeys (Atencio et al 2007) also reported the presence of a sustained discharge mechanism responding to FM stimuli. Thus FM responses in awake A1 were more complicated than under anesthesia.…”
mentioning
confidence: 90%
“…Suga and his colleagues (Edamatsu et al 1989;O'Neill and Suga 1982;Tsuzuki and Suga 1988) have conducted such experiments on awake bats and found that neuronal responses to particular aspects of FM stimuli, a crucial component of the bat's biosonar system, are topographically organized in the auditory cortex. To date, only two studies have been conducted on common mammals lacking acoustic specialization: a pioneering study on awake cats (Whitfield and Evans 1965) and a recent study on awake owl monkeys (Atencio et al 2007). About four decades ago, Whitfield and Evans (1965) reported the presence of multiple FM response types in cat primary auditory cortex (A1) and qualitatively categorized them into four classes: 1) the cells commenced firing as a FM tone crossed the boundary into its TRF and continued to fire until it left; 2) the cells started and ceased firing when FM tones were wholly within TRF; 3) the cells fired when the FM tone was outside TRF; 4) the cells responded to FM tones, but not to steady tones.…”
Section: Introductionmentioning
confidence: 99%